2011
DOI: 10.1186/1471-2334-11-256
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study on severe malaria among in-patients at Bombo regional hospital, Tanga, north-eastern Tanzania

Abstract: BackgroundIn Tanzania, malaria is the major cause of morbidity and mortality, accounting for about 30% of all hospital admissions and around 15% of all hospital deaths. Severe anaemia and cerebral malaria are the two main causes of death due to malaria in Tanga, Tanzania.MethodsThis was a prospective observational hospital-based study conducted from October 2004 to September 2005. Consent was sought from study participants or guardians in the wards. Finger prick blood was collected from each individual for thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…In Tanzania, the clinical manifestations of severe malaria in children younger than five years were cerebral malaria (47.3%) and severe anaemia (14.6%) [4]. Severe anaemia (8.57%) and circulatory collapse (11.90%) were the most common manifestations of severe malaria in neighbouring Ethiopia [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Tanzania, the clinical manifestations of severe malaria in children younger than five years were cerebral malaria (47.3%) and severe anaemia (14.6%) [4]. Severe anaemia (8.57%) and circulatory collapse (11.90%) were the most common manifestations of severe malaria in neighbouring Ethiopia [13].…”
Section: Discussionmentioning
confidence: 99%
“…In Tanzania, the fatality rate of severe malaria was 3.2% and the majority of deaths occurred in children younger than five years [4]. High mortality rates (33.3%), mainly in young adults, were observed among patients with severe malaria at Dakar, Senegal [23].…”
Section: Discussionmentioning
confidence: 99%
“…Presumptive treatment of fever with antimalarial drugs is still frequent in public health settings of sub-Saharan Africa, even in countries where ACTs, bed nets, malaria diagnosis and IPT are freely provided to vulnerable population [8]. During the last years, the prevalence of fever due to malaria has been drastically reduced in several countries including Gabon [3,6].…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of complicated malaria should also be influenced by interventions. Therefore, the decline of malaria prevalence can also result in a parallel decrease of, or influence the frequency of cerebral malaria (CM) and severe malarial anaemia (SMA) as reported in north-eastern Tanzania and in rural Kenya [8,9]. …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, cases attended by CORPs did not decline as for the slide positivity rates, thus most of the fevers could possibly be due to other infections [27-30]. Studies conducted in this and other areas of north-eastern Tanzania have shown low slide positivity rates for malaria and bacterial infections among children with severe febrile illnesses, suggesting that the causes of most fevers are not clearly known [28-32] (and C Mahende, pers. comm.…”
Section: Discussionmentioning
confidence: 99%